Paradoxe Aushandlungen von Migration im Diskurs um die Leipziger Eisenbahnstraße Paradoxical negotiations of migration in discourses around the Eisenbahnstraße in the city of Leipzig - Wiest, Karin; Kirndörfer, Elisabeth (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
Urban diversity discourses imply paradoxical configurations which, especially on the level of urban neighbourhoods, can be read as the inclusion of desired migration in connection with the exclusion of non-desired migration. In order to focus on novel shifts or rather the reciprocal conditioning of social in- and exclusions in the process of the internationalization and diversification of cities, the authors refer to the notion of paradox in the sense of a heuristic approach. Based on this, the paper examines seemingly contradictory in- and exclusions of migration in a long-standing key area of urban development policies. An analysis of the local media coverage and urban development documents demonstrates that in the discourse around Leipzig’s “Eisenbahnstraße”, a classical discursive figure is reproduced. It debates migration on the one hand as economic resource and problematises it, on the other, as a factor of unproductive deviance. Because of the fact that forms of social participation are bound to exclusions and control elsewhere, apparently paradoxical discursive logics emerge in the dealing with a pluralised urban space strongly shaped through migration. The fact that the invocation of a “parallel world” is explicitly directed towards a migrant population while the discourse on the “city of diversity” remains diffuse and largely anonymous, contradicts the general recognition of the realities of plural immigration societies. Despite or rather due to Leipzig’s pioneering role as regards to migration in the Eastern German context, migration (still) lacks the matter of course and remains a highly sensitive issue.
Keywords: Integration policies; Postmigrant society; Media discourse; Urban development; Leipzig; Eastern Germany